Semiquantitative slab view display for visual evaluation of 123I-FP-CIT SPECT. Issue 5 (May 2016) - Buchert, Ralph; Hutton, Chloe; Lange, Catharina; Hoppe, Peter; Makowski, Marcus; Bamousa, Thamer; Platsch, Günther; Brenner, Winfried; Declerck, Jerome
Abstract : Objective: Dopamine transporter single-photon emission computed tomography (SPECT) with 123 I-FP-CIT is used widely in the diagnosis of clinically uncertain parkinsonian syndromes. In terms of the evaluation of FP-CIT SPECT, some practice guidelines state that visual interpretation alone is generally sufficient in clinical patient care, whereas other guidelines consider semiquantitative analysis of striatal dopamine transporter availability mandatory. This discrepancy might be because of a relative lack of widely available display tools for FP-CIT SPECT. In this study, we evaluate a semiquantitative slab view display optimized for visual evaluation of FP-CIT SPECT that might resolve the discrepancy. Patients and methods: The reconstructed FP-CIT SPECT image was stereotactically normalized and scaled voxel by voxel to the mean uptake in the entire brain without striata. From the resulting distribution volume ratio image, a 12-mm-thick transversal slice (slab) through the striata was displayed with a standard colour table with predefined fixed thresholds on the distribution volume ratio. Visual scoring of the semiquantitative slab view was performed twice by four independent readers in 235 unselected patients. The specific binding ratio in the caudate and putamen was computed by fully automated semiquantitative analysis with predefined standard regions of interest in template space. Results: Intrarater and inter-rater agreement of binary visual categorization as 'normal' or 'reduced' was excellent (mean Cohen's κ =0.88 and 0.83, respectively). The area under the receiver–operator characteristic curve of the specific putamen-binding ratio for differentiation between visually normal and visually reduced (majority read) was 0.96. Conclusion: Visual interpretation of FP-CIT SPECT on the basis of the semiquantitative slab view display provides excellent stability within and between readers as well as very high agreement with semiquantitative analysis. This suggests that the slab view display enables reliable visual interpretation of FP-CIT SPECT in clinical routine patient care.